A Chemical Reaction Network to Generate Random, Power-Law-Distributed Time Intervals - Krauß, Patrick; Schulze, Holger; Metzner, Claus (Artificial Life, 2017)
In Lévy walks (LWs), particles move with a fixed speed along straight line segments and turn in new directions after random time intervals that are distributed according to a power law. Such LWs are thought to be an advantageous foraging and search strategy for organisms. While complex nervous systems are certainly capable of producing such behavior, it is not clear at present how single-cell organisms can generate the long-term correlated control signals required for a LW. Here, we construct a biochemical reaction system that generates long-time correlated concentration fluctuations of a signaling substance, with a tunable fractional exponent of the autocorrelation function. The network is based on well-known modules, and its basic function is highly robust with respect to the parameter settings.
EVALuna2:33191

Acute and Long-Term Circuit-Level Effects in the Auditory Cortex After Sound Trauma - Jeschke, Marcus; Happel, Max F.K.; Tziridis, Konstantin; Krauß, Patrick; Schilling, Achim; Schulze, Holger; Ohl, Frank W. (Frontiers in Neuroscience, 2021)
Harmful environmental sounds are a prevailing source of chronic hearing impairments, including noise induced hearing loss, hyperacusis, or tinnitus. How these symptoms are related to pathophysiological damage to the sensory receptor epithelia and its effects along the auditory pathway, have been documented in numerous studies. An open question concerns the temporal evolution of maladaptive changes after damage and their manifestation in the balance of thalamocortical and corticocortical input to the auditory cortex (ACx). To address these issues, we investigated the loci of plastic reorganizations across the tonotopic axis of the auditory cortex of male Mongolian gerbils (Meriones unguiculatus) acutely after a sound trauma and after several weeks. We used a residual current-source density analysis to dissociate adaptations of intracolumnar input and horizontally relayed corticocortical input to synaptic populations across cortical layers in ACx. A pure tone-based sound trauma caused acute changes of subcortical inputs and corticocortical inputs at all tonotopic regions, particularly showing a broad reduction of tone-evoked inputs at tonotopic regions around the trauma frequency. At other cortical sites, the overall columnar activity acutely decreased, while relative contributions of lateral corticocortical inputs increased. After 4–6 weeks, cortical activity in response to the altered sensory inputs showed a general increase of local thalamocortical input reaching levels higher than before the trauma. Hence, our results suggest a detailed mechanism for overcompensation of altered frequency input in the auditory cortex that relies on a changing balance of thalamocortical and intracortical input and along the frequency gradient of the cortical tonotopic map.
CRIS-Team Scopus Importer:2021-01-29
Keywords: auditory cortex; circuit level analysis; corticocortical; noise-induced hearing loss; thalamocortical

Adaptive stochastic resonance for unknown and variable input signals - Krauß, Patrick; Metzner, Claus; Schilling, Achim; Schütz, Christian; Tziridis, Konstantin; Fabry, Ben; Schulze, Holger (Scientific Reports, 2017)

A Founder Mutation in EHD1 Presents with Tubular Proteinuria and Deafness - Issler, Naomi; Afonso, Sara; Weissman, Irith; Jordan, Katrin; Cebrian-Serrano, Alberto; Meindl, Katrin; Dahlke, Eileen; Tziridis, Konstantin; Yan, Guanhua; Robles-López, José M.; Tabernero, Lydia; Patel, Vaksha; et al. (Journal of the American Society of Nephrology, 2022)
BACKGROUND: The endocytic reabsorption of proteins in the proximal tubule requires a complex machinery and defects can lead to tubular proteinuria. The precise mechanisms of endocytosis and processing of receptors and cargo are incompletely understood. EHD1 belongs to a family of proteins presumably involved in the scission of intracellular vesicles and in ciliogenesis. However, the relevance of EHD1 in human tissues, in particular in the kidney, was unknown. METHODS: Genetic techniques were used in patients with tubular proteinuria and deafness to identify the disease-causing gene. Diagnostic and functional studies were performed in patients and disease models to investigate the pathophysiology. RESULTS: We identified six individuals (5-33 years) with proteinuria and a high-frequency hearing deficit associated with the homozygous missense variant c.1192C>T (p.R398W) in EHD1. Proteinuria (0.7-2.1 g/d) consisted predominantly of low molecular weight proteins, reflecting impaired renal proximal tubular endocytosis of filtered proteins. Ehd1 knockout and Ehd1R398W/R398W knockin mice also showed a high-frequency hearing deficit and impaired receptor-mediated endocytosis in proximal tubules, and a zebrafish model showed impaired ability to reabsorb low molecular weight dextran. Interestingly, ciliogenesis appeared unaffected in patients and mouse models. In silico structural analysis predicted a destabilizing effect of the R398W variant and possible inference with nucleotide binding leading to impaired EHD1 oligomerization and membrane remodeling ability. CONCLUSIONS: A homozygous missense variant of EHD1 causes a previously unrecognized autosomal recessive disorder characterized by sensorineural deafness and tubular proteinuria. Recessive EHD1 variants should be considered in individuals with hearing impairment, especially if tubular proteinuria is noted.
CRIS-Team Scopus Importer:2022-04-22
Keywords: epithelial transport physiology; Eps15 homology domain; genetic renal disease; infertility; megalin; mutation; proximal tubule

Analysis and visualization of sleep stages based on deep neural networks - Krauß, Patrick; Metzner, Claus; Joshi, Nidhi; Schulze, Holger; Traxdorf, Maximilian; Maier, Andreas; Schilling, Achim (Neurobiology of Sleep and Circadian Rhythms, 2021)
Automatic sleep stage scoring based on deep neural networks has come into focus of sleep researchers and physicians, as a reliable method able to objectively classify sleep stages would save human resources and simplify clinical routines. Due to novel open-source software libraries for machine learning, in combination with enormous recent progress in hardware development, a paradigm shift in the field of sleep research towards automatic diagnostics might be imminent. We argue that modern machine learning techniques are not just a tool to perform automatic sleep stage classification, but are also a creative approach to find hidden properties of sleep physiology. We have already developed and established algorithms to visualize and cluster EEG data, facilitating first assessments on sleep health in terms of sleep-apnea and consequently reduced daytime vigilance. In the following study, we further analyze cortical activity during sleep by determining the probabilities of momentary sleep stages, represented as hypnodensity graphs and then computing vectorial cross-correlations of different EEG channels. We can show that this measure serves to estimate the period length of sleep cycles and thus can help to find disturbances due to pathological conditions.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Artificial neural networks; Deep learning; Electroencephalography (EEG); Hypnodensity graphs; Multidimensional scaling (MDS); Polysomnography (PSG); Sleep cycle analysis; Sleep stage scoring

Analysis of Audiometric Differences of Patients with and without Tinnitus in a Large Clinical Database - Gollnast, Dominik; Tziridis, Konstantin; Krauß, Patrick; Schilling, Achim; Hoppe, Ulrich; Schulze, Holger (Frontiers in Neurology, 2017)
Human hearing loss (HL) and comorbidities like tinnitus pose serious problems for people's daily life, which in most severe cases may lead to social isolation, depression, and suicide. Here, we investigate the relationship between hearing deficits and tinnitus. To this end, we conducted a retrospective study on anonymized pure tone and speech audiometric data from patients of the ENT hospital Erlangen in which we compare audiometric data between patients with and without tinnitus. Overall data from 37,661 patients with sensorineural (SHL) or conductive HL (CHL) with (T, 9.5%) or without (NT, 90.5%) a tinnitus percept in different age groups and with different tinnitus pitches were included in this study. The results of the pure tone audiometry comparisons showed significant differences in T patients compared to NT patients. In young patients, we generally found lower hearing thresholds in T compared to NT patients. In adult patients, differences were more heterogeneous: hearing thresholds in T patients were lower in low frequency ranges, while they were higher at high frequencies. Furthermore, lower thresholds were more often found in CHL patients and could rarely be detected in SHL patients. In speech audiometry, only CHL patients with high-pitched tinnitus showed lower thresholds compared to NT patients' thresholds. The results of this study may point to a biologically plausible functional benefit on hearing thresholds in HL tinnitus patients. We hypothesize that the physiological mechanism of stochastic resonance counteracts HL by adding neuronal noise to the system. This neuronal noise may induce changes in the auditory pathway and finally-as a side effect of threshold improvement-lead to the development of a tinnitus percept. We propose a general model of changed hearing thresholds in T patients, being either decreased or increased compared to NT patients.
EVALuna2:33169

Analysis of Multichannel EEG Patterns During Human Sleep: A Novel Approach - Krauß, Patrick; Schilling, Achim; Bauer, Judith; Tziridis, Konstantin; Metzner, Claus; Schulze, Holger; Traxdorf, Maximilian (Frontiers in Human Neuroscience, 2018)
Classic visual sleep stage scoring is based on electroencephalogram (EEG) frequency band analysis of 30 s epochs and is commonly performed by highly trained medical sleep specialists using additional information from submental EMG and eye movements electrooculogram (EOG). In this study, we provide the proof-of-principle in 40 subjects that sleep stages can be consistently differentiated solely on the basis of spatial 3-channel EEG patterns based on root-mean-square (RMS) amplitudes. The polysomnographic 3-channel EEG data are pre-processed by RMS averaging over intervals of 30 s leading to spatial cortical activity patterns represented by 3-dimensional vectors. These patterns are visualized using multidimensional scaling (MDS), allowing a comparison of the spatial cortical activity patterns with the conventional visual sleep scoring system according to the American Academy of Sleep Medicine (AASM). Spatial cortical activity patterns based on RMS amplitudes naturally divide into different clusters that correspond to visually scored sleep stages. Furthermore, these clusters are reproducible between different subjects. Especially the cluster associated with the REM sleep stage seems to be very different from the one associated with the wake state. This study provides a proof-of-principle that it is possible to separate sleep stages solely by analyzing spatially distributed EEG RMS amplitudes reflecting cortical activity and without classical EEG feature extractions like power spectrum analysis.
EVALuna2:35750

Analysis of Structure and Dynamics in Three-Neuron Motifs - Krauß, Patrick; Zankl, Alexandra; Schilling, Achim; Schulze, Holger; Metzner, Claus (Frontiers in Computational Neuroscience, 2019)
Recurrent neural networks can produce ongoing state-to-state transitions without any driving inputs, and the dynamical properties of these transitions are determined by the neuronal connection strengths. Due to non-linearity, it is not clear how strongly the system dynamics is affected by discrete local changes in the connection structure, such as the removal, addition, or sign-switching of individual connections. Moreover, there are no suitable metrics to quantify structural and dynamical differences between two given networks with arbitrarily indexed neurons. In this work, we present such permutation-invariant metrics and apply them to motifs of three binary neurons with discrete ternary connection strengths, an important class of building blocks in biological networks. Using multidimensional scaling, we then study the similarity relations between all 3,411 topologically distinct motifs with regard to structure and dynamics, revealing a strong clustering and various symmetries. As expected, the structural and dynamical distance between pairs of motifs show a significant positive correlation. Strikingly, however, the key parameter controlling motif dynamics turns out to be the ratio of excitatory to inhibitory connections.
CRIS-Team WoS Importer:2019-02-27

A New Statistical Approach for the Evaluation of Gap-prepulse Inhibition of the Acoustic Startle Reflex (GPIAS) for Tinnitus Assessment - Schilling, Achim; Krauß, Patrick; Gerum, Richard; Metzner, Claus; Tziridis, Konstantin; Schulze, Holger (Frontiers in Behavioral Neuroscience, 2017)
Background: An increasingly used behavioral paradigm for the objective assessment of a possible tinnitus percept in animal models has been proposed by Turner and coworkers in 2006. It is based on gap-prepulse inhibition (PPI) of the acoustic startle reflex (ASR) and usually referred to as GPIAS. As it does not require conditioning it became the method of choice to study neuroplastic phenomena associated with the development of tinnitus.Objective:It is still controversial if GPIAS is really appropriate for tinnitus screening, as the hypothesis that a tinnitus percept impairs the gap detection ability ("filling-in interpretation" is still questioned. Furthermore, a wide range of criteria for positive tinnitus detection in GPIAS have been used across different laboratories and there still is no consensus on a best practice for statistical evaluation of GPIAS results. Current approaches are often based on simple averaging of measured PPI values and comparisons on a population level without the possibility to perform valid statistics on the level of the single animal.Methods:A total number of 32 animals were measured using the standard GPIAS paradigm with varying number of measurement repetitions. Based on this data further statistical considerations were performed.Results:We here present a new statistical approach to overcome the methodological limitations of GPIAS. In a first step we show that ASR amplitudes are not normally distributed. Next we estimate the distribution of the measured PPI values by exploiting the full combinatorial power of all measured ASR amplitudes. We demonstrate that the amplitude ratios (1-PPI) are approximately lognormally distributed, allowing for parametrical testing of the logarithmized values and present a new statistical approach allowing for a valid and reliable statistical assessment of PPI changes in GPIAS.Conclusion:Based on our statistical approach we recommend using a constant criterion, which does not systematically depend on the number of measurement repetitions, in order to divide animals into a tinnitus and a non-tinnitus group. In particular, we recommend using a constant threshold based on the effect size as criterion, as the effect size, in contrast to thep-value, does not systematically depend on the number of measurement repetitions.
EVALuna2:33208

A statistical method for analyzing and comparing spatiotemporal cortical activation patterns - Krauß, Patrick; Metzner, Claus; Schilling, Achim; Tziridis, Konstantin; Traxdorf, Maximilian; Wollbrink, Andreas; Rampp, Stefan; Pantev, Christo; Schulze, Holger (Scientific Reports, 2018)
Information in the cortex is encoded in spatiotemporal patterns of neuronal activity, but the exact nature of that code still remains elusive. While onset responses to simple stimuli are associated with specific loci in cortical sensory maps, it is completely unclear how the information about a sustained stimulus is encoded that is perceived for minutes or even longer, when discharge rates have decayed back to spontaneous levels. Using a newly developed statistical approach (multidimensional cluster statistics (MCS)) that allows for a comparison of clusters of data points in n-dimensional space, we here demonstrate that the information about long-lasting stimuli is encoded in the ongoing spatiotemporal activity patterns in sensory cortex. We successfully apply MCS to multichannel local field potential recordings in different rodent models and sensory modalities, as well as to human MEG and EEG data, demonstrating its universal applicability. MCS thus indicates novel ways for the development of powerful read-out algorithms of spatiotemporal brain activity that may be implemented in innovative brain-computer interfaces (BCI).
EVALuna2:35749

Behavioral Assessment of Zwicker Tone Percepts in Gerbils - Schilling, Achim; Tziridis, Konstantin; Schulze, Holger; Krauß, Patrick (Neuroscience, 2023)
The Zwicker tone illusion – an auditory phantom percept after hearing a notched noise stimulus – can serve as an interesting model for acute tinnitus. Recent mechanistic models suggest that the underlying neural mechanisms of both percepts are similar. To date it is not clear if animals do perceive the Zwicker tone, as up to now no behavioral paradigms are available to objectively assess the presence of this phantom percept. Here we introduce, for the first time, a modified version of the gap pre-pulse inhibition of the acoustic startle reflex (GPIAS) paradigm to test if it is possible to induce a Zwicker tone percept in our rodent model, the Mongolian gerbil. Furthermore, we developed a new aversive conditioning learning paradigm and compare the two approaches. We found a significant increase in the GPIAS effect when presenting a notched noise compared to white noise gap pre-pulse inhibition, which is consistent with the interpretation of a Zwicker tone percept in these animals. In the aversive conditioning learning paradigm, no clear effect could be observed in the discrimination performance of the tested animals. When investigating the first 33% of the correct conditioned responses, an effect of a possible Zwicker tone percept can be seen, i.e. animals show identical behavior as if a pure tone was presented, but the paradigm needs to be further improved. Nevertheless, the results indicate that Mongolian gerbils are able to perceive a Zwicker tone and can serve as a neurophysiological model for human tinnitus generation.
CRIS-Team Scopus Importer:2023-05-05
Keywords: acoustic startle reflex; auditory phantom perception; aversive conditioning; shuttle box; tinnitus; Zwicker tone

Circadian Sensitivity of Noise Trauma-Induced Hearing Loss and Tinnitus in Mongolian Gerbils - Grimm, Jannik; Schulze, Holger; Tziridis, Konstantin (Frontiers in Neuroscience, 2022)
Noise-induced hearing loss (HL) has a circadian component: In nocturnal mice, hearing thresholds (HT) have a significantly stronger effect to acoustic trauma when induced during the night compared to rather mild effects on hearing when induced during daytime. Here, we investigate whether such effects are also present in diurnal Mongolian gerbils and determined whether trauma-induced HL correlated with the development of a tinnitus percept in these animals. In particular, we investigated the effects of acoustic trauma (2 kHz, 115 dB SPL, 75 min) on HT and tinnitus development in 34 male gerbils exposed either at 9 AM, 1 PM, 5 PM, or 12 PM. HT was measured by acoustic brainstem response audiometry at defined times 1 day before and 1 week after the trauma. Possible tinnitus percepts were assessed behaviorally by the gap prepulse inhibition of the acoustic startle response at defined times 1 day before and 1 week after the trauma. We found daytime-dependent changes due to trauma in mean HT in a frequency-dependent manner comparable to the results in mice, but the results temporally shifted according to respective activity profiles. Additionally, we found linear correlations of these threshold changes with the strength of the tinnitus percept, with the most prominent correlations in the 5 PM trauma group. Taken together, circadian sensitivity of the HT to noise trauma can also be found in gerbils, and tinnitus strength correlates most strongly with HL only when the trauma is applied at the most sensitive times, which seem to be the evening.
CRIS-Team WoS Importer:2022-07-01

Classification at the accuracy limit: facing the problem of data ambiguity - Metzner, Claus; Schilling, Achim; Traxdorf, Maximilian; Tziridis, Konstantin; Maier, Andreas; Schulze, Holger; Krauß, Patrick (Scientific Reports, 2022)
Data classification, the process of analyzing data and organizing it into categories or clusters, is a fundamental computing task of natural and artificial information processing systems. Both supervised classification and unsupervised clustering work best when the input vectors are distributed over the data space in a highly non-uniform way. These tasks become however challenging in weakly structured data sets, where a significant fraction of data points is located in between the regions of high point density. We derive the theoretical limit for classification accuracy that arises from this overlap of data categories. By using a surrogate data generation model with adjustable statistical properties, we show that sufficiently powerful classifiers based on completely different principles, such as perceptrons and Bayesian models, all perform at this universal accuracy limit under ideal training conditions. Remarkably, the accuracy limit is not affected by certain non-linear transformations of the data, even if these transformations are non-reversible and drastically reduce the information content of the input data. We further compare the data embeddings that emerge by supervised and unsupervised training, using the MNIST data set and human EEG recordings during sleep. We find for MNIST that categories are significantly separated not only after supervised training with back-propagation, but also after unsupervised dimensionality reduction. A qualitatively similar cluster enhancement by unsupervised compression is observed for the EEG sleep data, but with a very small overall degree of cluster separation. We conclude that the handwritten letters in MNIST can be considered as ’natural kinds’, whereas EEG sleep recordings are a relatively weakly structured data set, so that unsupervised clustering will not necessarily re-cover the human-defined sleep stages.
CRIS-Team Scopus Importer:2023-03-07

Cross-modal stochastic resonance as a universal principle to enhance sensory processing. - Krauß, Patrick; Tziridis, Konstantin; Schilling, Achim; Schulze, Holger (Frontiers in Neuroscience, 2018)

Cross-Modal Stochastic Resonance as a Universal Principle to Enhance Sensory Processing. - Krauß, Patrick; Tziridis, Konstantin; Schilling, Achim; Schulze, Holger (Frontiers in Neuroscience, 2018)
EVALuna2:210449

Deep brain stimulation in tinnitus: current and future perspectives - Smit, J. V.; Janssen, M. L. F.; Schulze, Holger; Jahanshahi, A.; Van Ouerbeeke, J. J.; Temel, Y.; Stokroos, R. J. (Brain Research, 2015)
Chronic tinnitus, also known as ringing in the ears, affects up to 15% of the adults and causes a serious socio-economic burden. At present, there is no treatment available which substantially reduces the perception of this phantom sound. In the past few years, preclinical and clinical studies have unraveled central mechanisms involved in the pathophysiology of tinnitus, replacing the classical periphery-based hypothesis. In subcortical auditory and non-auditory regions, increased spontaneous activity, neuronal bursting and synchrony were found. When reaching the auditory cortex, these neuronal alterations become perceptually relevant and consequently are perceived as phantom sound. A therapy with a potential to counteract deeply located pathological activity is deep brain stimulation, which has already been demonstrated to be effective in neurological diseases such as Parkinson's disease. In this review, several brain targets are discussed as possible targets for deep brain stimulation in tinnitus. The potential applicability of this treatment in tinnitus is discussed with examples from the preclinical field and clinical case studies.
EVALuna2:19976

Deficit in acoustic signal-in-noise detection in glycine receptor ?3 subunit knockout mice - Tziridis, Konstantin; Buerbank, Stefanie; Eulenburg, Volker; Dlugaiczyk, Julia; Schulze, Holger (European Journal of Neuroscience, 2017)
Hearing is an essential sense for communication in animals and humans. Normal function of the cochlea of higher vertebrates relies on a fine-tuned interplay of afferent and efferent innervation of both inner and outer hair cells. Efferent inhibition is controlled via olivocochlear feedback loops, mediated mainly by acetylcholine, ?-aminobutyric acid (GABA) and glycine, and is one of the first sites affected by synapto- and neuropathy in the development of hearing loss. While the functions of acetylcholine, GABA and other inhibitory transmitters within these feedback loops are at least partially understood, especially the function of glycine still remains elusive. To address this question, we investigated hearing in glycine receptor (GlyR) ?3 knockout (KO) and wildtype (WT) mice. We found no differences in pure tone hearing thresholds at 11.3 and 16 kHz between the two groups as assessed by auditory brainstem response (ABR) measurements. Detailed analysis of the ABR waves at 11.3 kHz, however, revealed a latency decrease of wave III and an amplitude increase of wave IV in KO compared to WT animals. GlyR?3 KO animals showed significantly impaired prepulse inhibition of the auditory startle response in a noisy environment, indicating that GlyR?3-mediated glycinergic inhibition is important for signal-in-noise detection.
EVALuna2:4772

Erlanger Modell der Tinnitusentstehung – Perspektivwechsel und neue Behandlungsstrategie - Schulze, Holger; Schilling, Achim; Krauß, Patrick; Tziridis, Konstantin (HNO, 2023)
Background: About one sixth of the population of western industrialized nations suffers from chronic, subjective tinnitus, causing socioeconomic treatment and follow-up costs of almost 22 billion euros per year in Germany alone. According to the prevailing view, tinnitus develops as a consequence of a maladaptive neurophysiological process in the brain triggered by hearing loss. Objectives: The Erlangen model of tinnitus development presented here is intended to propose a comprehensive neurophysiological explanation for the initial occurrence of the phantom sound after hearing loss. Based on the model, a new treatment strategy will be developed. Materials and methods: The model summarized here is based on various animal and human physiological studies conducted in recent years. Results: The Erlangen model considers subjective tinnitus as a side effect of a physiological mechanism that permanently optimizes information transmission into the auditory system by means of stochastic resonance (SR) even in the healthy auditory system. In fact, hearing-impaired patients with tinnitus hear better on average than those without tinnitus. This unfamiliar perspective on the phantom percept may already help affected patients to cope better with their suffering. In addition, based on the model, low intensity noise tinnitus suppression (LINTS) has been developed as a new, individually adapted treatment strategy for tonal tinnitus and has already been successfully tested in patients. Conclusions: A possible limiting factor for the model and treatment strategy is the pitch of the tinnitus percept, which may require adjustments to the treatment strategy for frequencies above about 5 kHz.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Autocorrelation; Hearing optimization; Low intensity noise tinnitus suppression (LINTS); Rehabilitation; Stochastic resonance

Estimation of Tinnitus-Related Socioeconomic Costs in Germany - Tziridis, Konstantin; Friedrich, Jana; Brueggemann, Petra; Mazurek, Birgit; Schulze, Holger (International Journal of Environmental Research and Public Health, 2022)
Despite the high prevalence of tinnitus in Germany of nearly 12% of the general population, there have been no systematic studies on the socioeconomic costs for German society caused by tinnitus so far. Here we analyzed data from 258 chronic tinnitus patients-namely tinnitus severity and health utility index (HUI)-and correlated them with their tinnitus-related public health care costs, private expenses, and economic loss due to their tinnitus percept as assessed by questionnaires. We found correlations of the HUI with health care costs and calculated the mean socioeconomic costs per tinnitus patient in Germany. According to our most conservative estimate, these sum up to EUR 4798.91 per year. Of that EUR 2206.95 account for the public health care, EUR 290.45 are carried by the patient privately and the remaining EUR 2301.51 account for economical loss due to sick leave. With a prevalence of 5.5% with at least bothersome tinnitus, this sums up to 21.9 billion Euro per year and with 25.82 sick leave days; tinnitus patients miss work more than double the time of the average German employee (10.9 days). The findings fit within the cost ranges of studies from other European countries and the USA and show that the socioeconomic burden of this disease-like symptom is a global problem. In comparison with the costs of other major chronic diseases in Germany-such as chronic obstructive pulmonary diseases (ca. 16 billion Euro) or diabetes mellitus (ca. 42 billion Euro)-the relevance of the 'symptom' tinnitus for the German social economy becomes even more obvious.
CRIS-Team Scopus Importer:2022-09-09
Keywords: health utility index; hearing loss; socioeconomic costs; tinnitus; tinnitus questionnaire

Extracting continuous sleep depth from EEG data without machine learning - Metzner, Claus; Schilling, Achim; Traxdorf, Maximilian; Schulze, Holger; Tziridis, Konstantin; Krauß, Patrick (Neurobiology of Sleep and Circadian Rhythms, 2023)
The human sleep-cycle has been divided into discrete sleep stages that can be recognized in electroencephalographic (EEG) and other bio-signals by trained specialists or machine learning systems. It is however unclear whether these human-defined stages can be re-discovered with unsupervised methods of data analysis, using only a minimal amount of generic pre-processing. Based on EEG data, recorded overnight from sleeping human subjects, we investigate the degree of clustering of the sleep stages using the General Discrimination Value as a quantitative measure of class separability. Virtually no clustering is found in the raw data, even after transforming the EEG signals of each 30-s epoch from the time domain into the more informative frequency domain. However, a Principal Component Analysis (PCA) of these epoch-wise frequency spectra reveals that the sleep stages separate significantly better in the low-dimensional sub-space of certain PCA components. In particular the component C1(t) can serve as a robust, continuous ‘master variable’ that encodes the depth of sleep and therefore correlates strongly with the ‘hypnogram’, a common plot of the discrete sleep stages over time. Moreover, C1(t) shows persistent trends during extended time periods where the sleep stage is constant, suggesting that sleep may be better understood as a continuum. These intriguing properties of C1(t) are not only relevant for understanding brain dynamics during sleep, but might also be exploited in low-cost single-channel sleep tracking devices for private and clinical use.
CRIS-Team Scopus Importer:2023-06-02

Is phase locking crucial to improve hearing thresholds in tinnitus patients? - Schulze, Holger; Tziridis, Konstantin (European Journal of Neuroscience, 2023)
Temporal processing of auditory data plays a crucial role in our proposed model of tinnitus development through stochastic resonance (SR). The model assumes a physiological mechanism optimizing auditory information transmission (as quantified by autocorrelation [AC] analysis) into the brain by adding the optimal amount of neuronal noise to otherwise subthreshold signals. We hypothesize that this takes place at the second synapse of the auditory pathway in the dorsal cochlear nucleus (DCN). We propose that after hearing loss, this neuronal noise is increased in the affected frequency band to improve hearing thresholds at the cost of upward propagation of this added noise, which finally may be perceived as tinnitus. We already showed the improvement of hearing thresholds in a large population of patients. Until now, we did not investigate the differences in hearing thresholds based on the biological constraints of early auditory temporal processing (phase locking) that is only possible up to frequencies of 5 kHz. In this report, we grouped our patient database (N = 47,986) according to tinnitus pitch (TP) of below (TP<5kHz) or above (TP>5kHz) the 5 kHz limit or having no tinnitus (NT) and compared their mean audiograms. We found that TP<5kHz patients showed significantly better hearing thresholds than all other patient groups independent of age. No improvement was seen for TP>5kHz patients who even showed worse thresholds than NT patients for high frequencies. These results are further evidence for our SR model of tinnitus development and the existence of AC analysis at the level of the DCN.
CRIS-Team Scopus Importer:2023-06-02
Keywords: audiometry; autocorrelation; dorsal cochlear nucleus; stochastic resonance

Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses - Klotz, Lisa; Wendler, Olaf; Frischknecht, Renato; Shigemoto, Ryuichi; Schulze, Holger; Enz, Ralf (The FASEB Journal, 2019)
Glutamate is the major excitatory neurotransmitter in the CNS binding to a variety of glutamate receptors. Metabotropic glutamate receptors (mGluR1 to mGluR8) can act excitatory or inhibitory, depending on associated signal cascades. Expression and localization of inhibitory acting mGluRs at inner hair cells (IHCs) in the cochlea are largely unknown. Here, we analyzed expression of mGluR2, mGluR3, mGluR4, mGluR6, mGluR7, and mGluR8 and investigated their localization with respect to the presynaptic ribbon of IHC synapses. We detected transcripts for mGluR2, mGluR3, and mGluR4 as well as for mGluR7a, mGluR7b, mGluR8a, and mGluR8b splice variants. Using receptor-specific antibodies in cochlear wholemounts, we found expression of mGluR2, mGluR4, and mGluR8b close to presynaptic ribbons. Super resolution and confocal microscopy in combination with 3-dimensional reconstructions indicated a postsynaptic localization of mGluR2 that overlaps with postsynaptic density protein 95 on dendrites of afferent type I spiral ganglion neurons. In contrast, mGluR4 and mGluR8b were expressed at the presynapse close to IHC ribbons. In summary, we localized in detail 3 mGluR types at IHC ribbon synapses, providing a fundament for new therapeutical strategies that could protect the cochlea against noxious stimuli and excitotoxicity.-Klotz, L., Wendler, O., Frischknecht, R., Shigemoto, R., Schulze, H., Enz, R. Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses.
CRIS-Team Scopus Importer:2019-12-17
Keywords: cochlea; IHC; mGlu receptor; mGluR

Microstructure of cortical activity during sleep reflects respiratory events and state of daytime vigilance - Traxdorf, Maximilian; Krauß, Patrick; Schilling, Achim; Schulze, Holger; Tziridis, Konstantin (Somnologie, 2019)
Background: Besides visual sleep stage scoring, it is possible to separate sleep stages by analyzing spatially distributed three-channel electroencephalogram (EEG) root mean square (RMS) amplitudes. This approach allows qualitative and quantitative evaluation of sleep architecture. The aim of this study was to analyze the effect of apnea–hypopnea index (AHI) and state of vigilance on the microstructure of cortical activity during sleep using EEG cluster analysis. Materials and methods: In 31 obstructive sleep apnea (OSA) patients, cortical EEG patterns were recorded during polysomnography and subjected to EEG cluster analysis. The results were subsequently correlated to AHI as well as to subjective (Epworth Sleepiness Scale) and objective (pupillographic sleepiness test) daytime sleepiness using linear regression. In 18/31 patients, cortical EEG patterns were recorded again the following night during continuous positive airway pressure (CPAP) titration and compared to the results of the first night. Results: Linear regression analyses revealed dependencies of specific cortical EEG patterns on AHI (intra-cluster distance of N2 [p = 0.019], N3 [p = 0.024]; inter-cluster distance of wake-N2 [p = 0.046], wake-N3 [p = 0.047], N2–N3 [p = 0.021]) and on objective daytime sleepiness (wake intra-cluster distance [p = 0.047], inter-cluster distance of wake-N3 [p = 0.042]), but not on subjective daytime sleepiness. Specifically, an increase in EEG pattern variability was found in patients with high AHI values, which could be reduced by CPAP therapy. Conclusion: This new approach enables objective analysis and visualization of sleep macro- and microstructure. The variance of neuronal EEG signal patterns enables conclusions on the presence of pathological respiratory events and objectively measured daytime sleepiness.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Continuous positive airway pressure; Daytime sleepiness; Electroencephalography; Root mean square; Sleep apnea; obstructive

Models of tinnitus development. From cochlea to cortex - Krauß, Patrick; Schilling, Achim; Tziridis, Konstantin; Schulze, Holger (HNO, 2019)
The development of subjective tinnitus is still not mechanistically understood and existing models are controversially discussed. In this overview, the authors discuss three of the main models, all of which propose damage to the cochlea as the initial step in tinnitus development. Based on these models, apossible manifestation of tinnitus-related neuronal activity at the perceptually relevant level of the auditory pathway, the auditory cortex, is presented. Furthermore, it is demonstrated that one of the models offers anew view on the phenomenon, which could potentially help patients to better cope with their condition.
CRIS-Team WoS Importer:2019-03-26

Noise Trauma Induced Neural Plasticity Throughout the Auditory System of Mongolian Gerbils: Differences between Tinnitus Developing and Non-Developing Animals - Tziridis, Konstantin; Ahlf, Sönke; Jeschke, Marcus; Happel, Max F. K.; Ohl, Frank W.; Schulze, Holger (Frontiers in Neurology, 2015)
In this study, we describe differences between neural plasticity in auditory cortex (AC) of animals that developed subjective tinnitus (group T) after noise-induced hearing loss (NIHL) compared to those that did not [group non-tinnitus (NT)]. To this end, our analysis focuses on the input activity of cortical neurons based on the temporal and spectral analysis of local field potential (LFP) recordings and an in-depth analysis of auditory brainstem responses (ABR) in the same animals. In response to NIHL in NT animals we find a significant general reduction in overall cortical activity and spectral power as well as changes in all ABR wave amplitudes as a function of loudness. In contrast, T-animals show no significant change in overall cortical activity as assessed by root mean square analysis of LFP amplitudes, but a specific increase in LFP spectral power and in the amplitude of ABR wave V reflecting activity in the inferior colliculus (IC). Based on these results, we put forward a refined model of tinnitus prevention after NIHL that acts via a top-down global (i.e., frequency-unspecific) inhibition reducing overall neuronal activity in AC and IC, thereby counteracting NIHL-induced bottom-up frequency-specific neuroplasticity suggested in current models of tinnitus development.
EVALuna2:19969

Objective estimation of sensory thresholds based on neurophysiological parameters. - Schilling, Achim; Gerum, Richard; Krauß, Patrick; Metzner, Claus; Tziridis, Konstantin; Schulze, Holger (Frontiers in Neuroscience, 2019)

Objective estimation of sensory thresholds based on neurophysiological parameters - Schilling, Achim; Gerum, Richard; Krauß, Patrick; Metzner, Claus; Tziridis, Konstantin; Schulze, Holger (Frontiers in Neuroscience, 2019)
Reliable determination of sensory thresholds is the holy grail of signal detection theory. However, there exists no assumption-independent gold standard for the estimation of thresholds based on neurophysiological parameters, although a reliable estimation method is crucial for both scientific investigations and clinical diagnosis. Whenever it is impossible to communicate with the subjects, as in studies with animals or neonates, thresholds have to be derived from neural recordings or by indirect behavioral tests. Whenever the threshold is estimated based on such measures, the standard approach until now is the subjective setting-either by eye or by statistical means-of the threshold to the value where at least a “clear” signal is detectable. These measures are highly subjective, strongly depend on the noise, and fluctuate due to the low signal-to-noise ratio near the threshold. Here we show a novel method to reliably estimate physiological thresholds based on neurophysiological parameters. Using surrogate data we demonstrate that fitting the responses to different stimulus intensities with a hard sigmoid function, in combination with subsampling, provides a robust threshold value as well as an accurate uncertainty estimate. This method has no systematic dependence on the noise and does not even require samples in the full dynamic range of the sensory system. We prove that this method is universally applicable to all types of sensory systems, ranging from somatosensory stimulus processing in the cortex to auditory processing in the brain stem.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Auditory cortex; Auditory neuroscience; Automated threshold estimation; Electrophysiology; Hearing; Psychometric function; Somatosensation; Somatosensory cortex

Open(G)PIAS: An open-source solution for the construction of a high-precision acoustic startle response setup for tinnitus screening and threshold estimation in rodents - Gerum, Richard; Rahlfs, Hinrich; Streb, Matthias; Krauß, Patrick; Grimm, Jannik; Metzner, Claus; Tziridis, Konstantin; Günther, Michael; Schulze, Holger; Kellermann, Walter; Schilling, Achim (Frontiers in Behavioral Neuroscience, 2019)
The modulation of the acoustic startle reflex (ASR) by a pre-stimulus called pre-pulse inhibition (PPI, for gap of silence pre-stimulus: GPIAS) is a versatile tool to, e.g., estimate hearing thresholds or identify subjective tinnitus percepts in rodents. A proper application of these paradigms depends on a reliable measurement of the ASR amplitudes and an exact stimulus presentation in terms of frequency and intensity. Here, we introduce a novel open-source solution for the construction of a low-cost ASR setup. The complete software for data acquisition and stimulus presentation is written in Python 3.6 and is provided as an Anaconda package. Furthermore, we provide a construction plan for the sensor system based on low-cost hardware components. Exemplary GPIAS data from two animal models (Mus musculus, Meriones unguiculatus) show that the ratio histograms (1-GPIAS) of the gap-pre-stimulus and no pre-stimulus ASR amplitudes can be well described by a log-normal distribution being in good accordance to previous studies with already established setups. Furthermore, it can be shown that the PPI as a function of pre-stimulus intensity (threshold paradigm) can be approximated with a hard-sigmoid function enabling a reproducible sensory threshold estimation. Thus, we show that the open-source solution could help to further establish the ASR method in many laboratories and, thus, facilitate and standardize research in animal models of tinnitus and/or hearing loss.
CRIS-Team Scopus Importer:2019-07-16
Keywords: 3D acceleration sensor; Anaconda package; Animal model; Low-cost setup; Startle; Tinnitus

Pharmacologic treatments in preclinical tinnitus models with special focus on Ginkgo biloba leaf extract EGb 761® - Barth, Stephan W.; Lehner, Martin D.; Dietz, Gunnar P.H.; Schulze, Holger (Molecular and Cellular Neuroscience, 2021)
Tinnitus is defined as the perception of sound in the absence of external acoustic stimuli. Frequent comorbidities or associated factors are depression, anxiety, concentration problems, insomnia, resignation, helplessness, headache, bruxism, or social isolation, just to name a few. Although many therapeutic approaches have already been tested with varying success, there still is no cure available for tinnitus. The search for an effective treatment has been hampered by the fact that the mechanisms of tinnitus development are still not fully understood, although several models are available and discussed in this review. Our review will give a brief overview about preclinical models, presenting the heterogeneity of tinnitus sub-types depending on the different inner ear and brain structures involved in tinnitus etiology and pathogenesis. Based on these models we introduce the different target structures and transmitter systems implicated in tinnitus development and provide an extensive overview on preclinical drug-based therapeutic approaches that have been explored in various animal models. As the special extract from Ginkgo biloba leaves EGb 761® has been the most widely tested drug in both non-clinical tinnitus models as well as in clinical trials, a special focus will be given to EGb 761®. The efficacy of terpene lactones, flavone glycosides and proanthocyanidines with their distinct contribution to the overall efficacy profile of the multi-constituent drug EGb 761® will be discussed.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Gerbil; Hearing research; Inner ear; Medication; Mouse; Pharmacology; Plant extract; ginkgo; translational; Rat; Rodent model

Predictive coding and stochastic resonance as fundamental principles of auditory phantom perception - Schilling, Achim; Sedley, William; Gerum, Richard C.; Metzner, Claus; Tziridis, Konstantin; Maier, Andreas; Schulze, Holger; Zeng, Fan Gang; Friston, Karl J.; Krauß, Patrick (Brain, 2023)
Mechanistic insight is achieved only when experiments are employed to test formal or computational models. Furthermore, in analogy to lesion studies, phantom perception may serve as a vehicle to understand the fundamental processing principles underlying healthy auditory perception. With a special focus on tinnitus-as the prime example of auditory phantom perception-we review recent work at the intersection of artificial intelligence, psychology and neuroscience. In particular, we discuss why everyone with tinnitus suffers from (at least hidden) hearing loss, but not everyone with hearing loss suffers from tinnitus. We argue that intrinsic neural noise is generated and amplified along the auditory pathway as a compensatory mechanism to restore normal hearing based on adaptive stochastic resonance. The neural noise increase can then be misinterpreted as auditory input and perceived as tinnitus. This mechanism can be formalized in the Bayesian brain framework, where the percept (posterior) assimilates a prior prediction (brain's expectations) and likelihood (bottom-up neural signal). A higher mean and lower variance (i.e. enhanced precision) of the likelihood shifts the posterior, evincing a misinterpretation of sensory evidence, which may be further confounded by plastic changes in the brain that underwrite prior predictions. Hence, two fundamental processing principles provide the most explanatory power for the emergence of auditory phantom perceptions: predictive coding as a top-down and adaptive stochastic resonance as a complementary bottom-up mechanism. We conclude that both principles also play a crucial role in healthy auditory perception. Finally, in the context of neuroscience-inspired artificial intelligence, both processing principles may serve to improve contemporary machine learning techniques.
CRIS-Team Scopus Importer:2023-12-15
Keywords: artificial intelligence; Bayesian brain; phantom perception; predictive coding; stochastic resonance; tinnitus

Preventive Effects of Ginkgo-Extract EGb 761® on Noise Trauma-Induced Cochlear Synaptopathy - Tziridis, Konstantin; Schulze, Holger (Nutrients, 2022)
Noise trauma-induced loss of ribbon synapses at the inner hair cells (IHC) of the cochlea may lead to hearing loss (HL), resulting in tinnitus. We are convinced that a successful and sustainable therapy of tinnitus has to treat both symptom and cause. One of these causes may be the mentioned loss of ribbon synapses at the IHC of the cochlea. In this study, we investigated the possible preventive and curative effects of the Ginkgo biloba extract EGb 761® on noise-induced synaptopathy, HL, and tinnitus development in Mongolian gerbils (Meriones unguiculatus). To this end, 37 male animals received EGb 761® or placebo orally 3 weeks before (16 animals) or after (21 animals) a monaural acoustic noise trauma (2 kHz, 115 dB SPL, 75 min). Animals' hearing thresholds were determined by auditory brainstem response (ABR) audiometry. A possible tinnitus percept was assessed by the gap prepulse inhibition acoustic startle reflex (GPIAS) response paradigm. Synaptopathy was quantified by cochlear immunofluorescence histology, counting the ribbon synapses of 15 IHCs at 11 different cochlear frequency locations per ear. We found a clear preventive effect of EGb 761® on ribbon synapse numbers with the surprising result of a significant increase in synaptic innervation on the trauma side relative to placebo-treated animals. Consequently, animals treated with EGb 761® before noise trauma did not develop a significant HL and were also less affected by tinnitus compared to placebo-treated animals. On the other hand, we did not see a curative effect (EGb 761® treatment after noise trauma) of the extract on ribbon synapse numbers and, consequently, a significant HL and no difference in tinnitus development compared to the placebo-treated animals. Taken together, EGb 761® prevented noise-induced HL and tinnitus by protecting from noise trauma-induced cochlear ribbon synapse loss; however, in our model, it did not restore lost ribbon synapses.
CRIS-Team Scopus Importer:2022-08-12
Keywords: auditory brainstem response; gap prepulse inhibition of the acoustic startle response; hearing loss; immunohistology; pharmacological treatment; rodents; synaptopathy; tinnitus

Protective effects of Ginkgo biloba extract EGb 761 against noise trauma-induced hearing loss and tinnitus development - Tziridis, Konstantin; Korn, Sabine; Ahlf, Sönke; Schulze, Holger (Neural Plasticity, 2014)
Noise-induced hearing loss (NIHL) and resulting comorbidities like subjective tinnitus are common diseases in modern societies. A substance shown to be effective against NIHL in an animal model is the Ginkgo biloba extract EGb 761. Further effects of the extract on the cellular and systemic levels of the nervous system make it a promising candidate not only for protection against NIHL but also for its secondary comorbidities like tinnitus. Following an earlier study we here tested the potential effectiveness of prophylactic EGb 761 treatment against NIHL and tinnitus development in the Mongolian gerbil. We monitored the effects of EGb 761 and noise trauma-induced changes on signal processing within the auditory system by means of behavioral and electrophysiological approaches. We found significantly reduced NIHL and tinnitus development upon EGb 761 application, compared to vehicle treated animals. These protective effects of EGb 761 were correlated with changes in auditory processing, both at peripheral and central levels. We propose a model with two main effects of EGb 761 on auditory processing, first, an increase of auditory brainstem activity leading to an increased thalamic input to the primary auditory cortex (AI) and second, an asymmetric effect on lateral inhibition in AI.
EVALuna2:19933

Reduktion der Tinnituslautstärke: Pilotstudie zur Abschwächung von tonalem Tinnitus mit schwellennahem, individuell spektral optimiertem Rauschen - Schilling, Anne; Krauß, Patrick; Hannemann, R.; Schulze, Holger; Tziridis, Konstantin (HNO, 2020)
Background: Around 15% of the general population is affected by tinnitus, but no real cure exists despite intensive research. Based on our recent causal model for tinnitus development, we here test a new treatment aimed at counteracting the perception. This treatment is based on the stochastic resonance phenomenon at specific auditory system synapses that is induced by externally presented near-threshold noise. Objective: This pilot study will investigate whether individually spectrally adapted noise can successfully reduce chronic tonal/narrow-band tinnitus during stimulation. Materials and methods: Hearing loss (HL) as well as tinnitus pitch (TP) and loudness (TL) were audiometrically measured in 22 adults (46.6±16.3 years; 4 women) with tinnitus. Based on these measurements, up to eight different noise stimuli with five intensities (−20 to +20 dB SL) were generated. These were presented for 40 s each via audiologic headphones in a soundproof chamber. After each presentation, the change in TL was rated on a five-level scale (−2 to +2). Results: We found patients (n = 6) without any improvement in their TL perception as well as patients with improvement (n = 16), where stimulation around the TP was most effective. The groups differed in post-hoc analysis of their audiograms: the effectiveness of our new therapeutic strategy obviously depends on the individual HL, and was most effective in normal-hearing tinnitus patients and those with mild HL. Conclusion: Subjective TL could be reduced in 16 out of 22 patients during stimulation. For a possible success of a future therapy, the HL seems to be of relevance.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Hearing loss; Individualized therapy; Pure tone audiometry; Stochastic resonance; Tinnitus questionnaires

Restoration of function after cortical lesion: does it require an internal template? - Schulze, Holger; Tziridis, Konstantin (Neural Regeneration Research, 2014)
EVALuna2:19970

Salicylate-Induced Changes in Hearing Thresholds in Mongolian Gerbils Are Correlated With Tinnitus Frequency but Not With Tinnitus Strength - Lanaia, Veralice; Tziridis, Konstantin; Schulze, Holger (Frontiers in Behavioral Neuroscience, 2021)
Tinnitus is an auditory phantom percept without external sound sources. Despite the high prevalence and tinnitus-associated distress of affected patients, the pathophysiology of tinnitus remains largely unknown, making prevention and treatments difficult to develop. In order to elucidate the pathophysiology of tinnitus, animal models are used where tinnitus is induced either permanently by noise trauma or transiently by the application of salicylate. In a model of trauma-induced tinnitus, we have suggested a central origin of tinnitus-related development of neuronal hyperactivity based on stochastic resonance (SR). SR refers to the physiological phenomenon that weak subthreshold signals for given sensors (or synapses) can still be detected and transmitted if appropriate noise is added to the input of the sensor. The main objective of this study was to characterize the neurophysiological and behavioral effects during salicylate-induced tinnitus and compare these to the conditions within the trauma model. Our data show, in line with the pharmacokinetics, that hearing thresholds generally increase 2 h after salicylate injections. This increase was significantly stronger within the region of best hearing compared to other frequencies. Furthermore, animals showed behavioral signs of tinnitus during that time window and frequency range as assessed by gap prepulse inhibition of the acoustic startle reflex (GPIAS). In contrast to animals with noise trauma-induced tinnitus, salicylate-induced tinnitus animals showed no correlation between hearing thresholds and behavioral signs of tinnitus, indicating that the development of tinnitus after salicylate injection is not based on SR as proposed for the trauma model. In other words, salicylate-induced tinnitus and noise trauma-induced tinnitus are not based on the same neurophysiological mechanism.
CRIS-Team WoS Importer:2021-08-27

Sensory cortex lesion triggers compensatory neuronal plasticity - Depner, Manfred; Tziridis, Konstantin; Heß, Andreas; Schulze, Holger (BMC Neuroscience, 2014)
Lesions to the human brain often cause dramatic impairments in the life of patients because of the very limited capacity of the mammalian nervous system to regenerate. On the other hand, neuronal tissue has a high capacity to reorganize itself so that loss of function due to brain damage may be compensated through neuroplastic reorganization of undamaged tissue in brain regions adjacent or contralateral to the lesion site. In this study we investigated the effect of serial lesions of the auditory cortices (AC) in both hemispheres of Mongolian gerbils on discrimination performance for fast amplitude modulated tones (AM). Healthy animals were trained to discriminate two fast AM, an ability that has previously been shown to critically depend on cortical processing. Their ability to maintain significant discrimination performance was retested after unilateral AC lesion, and again after lesion of the contralateral AC, with 15 days of continuing training in between the two lesions.After bilateral cortical ablation of both AC and 45 days of training the animals show no change in pure tone detection threshold as measured with modulation of the acoustic startle reflex which has been shown to rely on subcortical structures. In contrast to simultaneous bilateral ablation of AC that results in complete loss of AM discrimination ability in this paradigm we found compensatory plasticity that seems to be triggered by unilateral cortical ablation with subsequent training and that is able to almost fully compensate for the lost cortical functions.Our results demonstrate that AM discrimination ability that normally depends on AC may be transferred to other brain regions when the brain has time to activate compensatory plasticity between the lesions of the two AC hemispheres. For this process to take place obviously one intact AC hemisphere is needed. This finding may open perspectives for new therapeutic strategies that may alleviate the impairments after multiple ischemic strokes.
EVALuna2:8518

Sleep as a random walk: a super-statistical analysis of EEG data across sleep stages - Metzner, Claus; Schilling, Achim; Traxdorf, Maximilian; Schulze, Holger; Krauß, Patrick (Communications Biology, 2021)
In clinical practice, human sleep is classified into stages, each associated with different levels of muscular activity and marked by characteristic patterns in the EEG signals. It is however unclear whether this subdivision into discrete stages with sharply defined boundaries is truly reflecting the dynamics of human sleep. To address this question, we consider one-channel EEG signals as heterogeneous random walks: stochastic processes controlled by hyper-parameters that are themselves time-dependent. We first demonstrate the heterogeneity of the random process by showing that each sleep stage has a characteristic distribution and temporal correlation function of the raw EEG signals. Next, we perform a super-statistical analysis by computing hyper-parameters, such as the standard deviation, kurtosis, and skewness of the raw signal distributions, within subsequent 30-second epochs. It turns out that also the hyper-parameters have characteristic, sleep-stage-dependent distributions, which can be exploited for a simple Bayesian sleep stage detection. Moreover, we find that the hyper-parameters are not piece-wise constant, as the traditional hypnograms would suggest, but show rising or falling trends within and across sleep stages, pointing to an underlying continuous rather than sub-divided process that controls human sleep. Based on the hyper-parameters, we finally perform a pairwise similarity analysis between the different sleep stages, using a quantitative measure for the separability of data clusters in multi-dimensional spaces.
CRIS-Team WoS Importer:2021-12-24

Special issues for the 55th Inner Ear Biology Workshop 06.–08.09.2018 in Berlin - Mazurek, B.; Knipper, M.; Biesinger, E.; Schulze, Holger (HNO, 2019)
CRIS-Team Scopus Importer:2019-06-28

Special Issues for the 55th Inner Ear Biology Workshop from 6th to 8th September 2018 in Berlin Basic Research and Clinical Aspects - translational Aspects of Hearing Research - Mazurek, B.; Knipper, M.; Biesinger, E.; Schulze, Holger (HNO, 2019)
CRIS-Team WoS Importer:2019-03-26

Spectrally Matched Near-Threshold Noise for Subjective Tinnitus Loudness Attenuation Based on Stochastic Resonance - Tziridis, Konstantin; Brunner, Sarah; Schilling, Achim; Krauß, Patrick; Schulze, Holger (Frontiers in Neuroscience, 2022)
Recently, we proposed a model of tinnitus development based on a physiological mechanism of permanent optimization of information transfer from the auditory periphery to the central nervous system by means of neuronal stochastic resonance utilizing neuronal noise to be added to the cochlear input, thereby improving hearing thresholds. In this view, tinnitus is a byproduct of this added neuronal activity. Interestingly, in healthy subjects auditory thresholds can also be improved by adding external, near-threshold acoustic noise. Based on these two findings and a pilot study we hypostatized that tinnitus loudness (TL) might be reduced, if the internally generated neuronal noise is substituted by externally provided individually adapted acoustic noise. In the present study, we extended the data base of the first pilot and further optimized our approach using a more fine-grained adaptation of the presented noise to the patients’ audiometric data. We presented different spectrally filtered near-threshold noises (−2 dB to +6 dB HL, 2 dB steps) for 40 s each to 24 patients with tonal tinnitus and a hearing deficit not exceeding 40 dB. After each presentation, the effect of the noise on the perceived TL was obtained by patient’s response to a 5-scale question. In 21 out of 24 patients (13 women) TL was successfully subjectively attenuated during acoustic near-threshold stimulation using noise spectrally centered half an octave below the individual’s tinnitus pitch (TP). Six patients reported complete subjective silencing of their tinnitus percept during stimulation. Acoustic noise is able to reduce TL, but the TP has to be taken into account. Based on our findings, we speculate about a possible future treatment of tinnitus by near-threshold bandpass filtered acoustic noise stimulation, which could be implemented in hearing aids with noise generators.
CRIS-Team Scopus Importer:2022-04-29
Keywords: individualized medicine; low intensity acoustic noise; stochastic resonance; tinnitus questionnaires; tinnitus treatment

Stochastic Resonance Controlled Upregulation of Internal Noise after Hearing Loss as a Putative Cause of Tinnitus-Related Neuronal Hyperactivity - Krauß, Patrick; Tziridis, Konstantin; Metzner, Claus; Schilling, Achim; Hoppe, Ulrich; Schulze, Holger (Frontiers in Neuroscience, 2016)
Subjective tinnitus is generally assumed to be a consequence of hearing loss. In animal studies it has been demonstrated that acoustic trauma induced cochlear damage can lead to behavioral signs of tinnitus. In addition it was shown that noise trauma may lead to deafferentation of cochlear inner hair cells (IHC) even in the absence of elevated hearing thresholds, and it seems conceivable that such hidden hearing loss may be sufficient to cause tinnitus. Numerous studies have indicated that tinnitus is correlated with pathologically increased spontaneous firing rates and hyperactivity of neurons along the auditory pathway. It has been proposed that this hyperactivity is the consequence of a mechanism aiming to compensate for reduced input to the auditory system by increasing central neuronal gain, a mechanism referred to as homeostatic plasticity (HP), thereby maintaining mean firing rates over longer timescales for stabilization of neuronal processing. Here we propose an alternative, new interpretation of tinnitus-related development of neuronal hyperactivity in terms of information theory. In particular, we suggest that stochastic resonance (SR) plays a key role in both short- and long-term plasticity within the auditory system and that SR is the primary cause of neuronal hyperactivity and tinnitus. We argue that following hearing loss, SR serves to lift signals above the increased neuronal thresholds, thereby partly compensating for the hearing loss. In our model, the increased amount of internal noise-which is crucial for SR to work-corresponds to neuronal hyperactivity which subsequently causes neuronal plasticity along the auditory pathway and finally may lead to the development of a phantom percept, i.e., subjective tinnitus. We demonstrate the plausibility of our hypothesis using a computational model and provide exemplary findings in human patients that are consistent with that model. Finally we discuss the observed asymmetry in human tinnitus pitch distribution as a consequence of asymmetry of the distribution of auditory nerve type I fibers along the cochlea in the context of our model.
EVALuna2:33193

Systems Medicine Approach for Tinnitus with Comorbid Disorders - Mazurek, Birgit; Rose, Matthias; Schulze, Holger; Dobel, Christian (Nutrients, 2022)
Despite the fact that chronic diseases usually occur together with a spectrum of possible comorbidities that may differ strongly between patients, they are classically still viewed as distinct disease entities and, consequently, are often treated with uniform therapies. Unfortunately, such an approach does not take into account that different combinations of symptoms and comorbidities may result from different pathological (e.g., environmental, genetic, dietary, etc.) factors, which require specific and individualised therapeutic strategies. In this opinion paper, we aim to put forward a more differentiated, systems medicine approach to disease and patient treatment. To elaborate on this concept, we focus on the interplay of tinnitus, depression, and chronic pain. In our view, these conditions can be characterised by a variety of phenotypes composed of variable sets of symptoms and biomarkers, rather than distinct disease entities. The knowledge of the interplay of such symptoms and biomarkers will provide the key to a deeper, mechanistic understanding of disease pathologies. This paves the way for prediction and prevention of disease pathways, including more personalised and effective treatment strategies.
CRIS-Team Scopus Importer:2022-11-11
Keywords: comorbidity; depression; pain; system medicine; tinnitus

The Neural Bases of Tinnitus: Lessons from Deafness and Cochlear Implants - Knipper, Marlies; van Dijk, Pim; Schulze, Holger; Mazurek, Birgit; Krauß, Patrick; Scheper, Verena; Warnecke, Athanasia; Schlee, Winfried; Schwabe, Kerstin; Singer, Wibke; Braun, Christoph; Delano, Paul H.; et al. (The Journal of Neuroscience, 2020)
Subjective tinnitus is the conscious perception of sound in the absence of any acoustic source. The literature suggests various tinnitus mechanisms, most of which invoke changes in spontaneous firing rates of central auditory neurons resulting from modification of neural gain. Here, we present an alternative model based on evidence that tinnitus is: (1) rare in people who are congenitally deaf, (2) common in people with acquired deafness, and (3) potentially suppressed by active cochlear implants used for hearing restoration. We propose that tinnitus can only develop after fast auditory fiber activity has stimulated the synapse formation between fast-spiking parvalbumin positive (PV+) interneurons and projecting neurons in the ascending auditory path and coactivated frontostriatal networks after hearing onset. Thereafter, fast auditory fiber activity promotes feedforward and feedback inhibition mediated by PV+ interneuron activity in auditory-specific circuits. This inhibitory network enables enhanced stimulus resolution, attention-driven contrast improvement, and augmentation of auditory responses in central auditory pathways (neural gain) after damage of slow auditory fibers. When fast auditory fiber activity is lost, tonic PV+ interneuron activity is diminished, resulting in the prolonged response latencies, sudden hyperexcitability, enhanced cortical synchrony, elevated spontaneous γ oscillations, and impaired attention/stress-control that have been described in previous tinnitus models. Moreover, because fast processing is gained through sensory experience, tinnitus would not exist in congenital deafness. Electrical cochlear stimulation may have the potential to reestablish tonic inhibitory networks and thus suppress tinnitus. The proposed framework unites many ideas of tinnitus pathophysiology and may catalyze cooperative efforts to develop tinnitus therapies.
CRIS-Team Scopus Importer:2020-09-25

Therapeutic Value of Ginkgo biloba Extract EGb 761® in an Animal Model (Meriones unguiculatus) for Noise Trauma Induced Hearing Loss and Tinnitus - Krauß, Patrick; Tziridis, Konstantin; Buerbank, Stefanie; Schilling, Achim; Schulze, Holger (PLoS ONE, 2016)
Noise induced hearing loss (NIHL) is a common disease in modern societies and may lead to maladaptations within the auditory system that finally result in subjective tinnitus. Available therapies may only alleviate the symptoms rather than restore normal hearing. In a previous study we demonstrated that the prophylactic application of Ginkgo biloba extract EGb 761® significantly reduces NIHL and tinnitus development in our Mongolian gerbil (Meriones unguiculatus) animal model. Here, we tested whether the application of EGb 761® has beneficial effects after the formation of permanent NIHL and tinnitus. To this end we monitored the therapeutic effects of EGb 761® on noise trauma-induced changes in signal processing within the auditory system of our animal model by behavioral (acoustic startle response, ASR) and electrophysiological approaches (auditory brainstem responses, ABR). We found that-in contrast to vehicle-three weeks of daily oral EGb 761® treatment (100 mg/kg body weight) led to a restoration of hearing thresholds back to pre-trauma conditions. In addition, all 9 animals that displayed behavioral signs of subjective tinnitus showed improvement, with 7 of them showing complete relief of tinnitus symptoms during the time of EGb 761® treatment. After discontinuation of EGb 761® treatment, tinnitus related behavior reappeared in all but one of these animals while auditory thresholds remained restored. A detailed analysis of ABR waves revealed that EGb 761® treatment did not simply change auditory processing back to pre-trauma conditions, but led to subtle changes of ABR wave amplitude and latency at different levels of the auditory pathway, with an overall increase of response to low stimulus intensities and a decrease at high intensities. The functional relevance of these changes may be the observed improvement of hearing thresholds while at the same time suppression of responses to high stimulus intensities may point to a global inhibitory mechanism that counteracts tinnitus.
EVALuna2:20023

The stochastic resonance model of auditory perception: A unified explanation of tinnitus development, Zwicker tone illusion, and residual inhibition - Schilling, Achim; Tziridis, Konstantin; Schulze, Holger; Krauß, Patrick (Progress in Brain Research, 2021)
Stochastic resonance (SR) has been proposed to play a major role in auditory perception, and to maintain optimal information transmission from the cochlea to the auditory system. By this, the auditory system could adapt to changes of the auditory input at second or even sub-second timescales. In case of reduced auditory input, somatosensory projections to the dorsal cochlear nucleus would be disinhibited in order to improve hearing thresholds by means of SR. As a side effect, the increased somatosensory input corresponding to the observed tinnitus-associated neuronal hyperactivity is then perceived as tinnitus. In addition, the model can also explain transient phantom tone perceptions occurring after ear plugging, or the Zwicker tone illusion. Vice versa, the model predicts that via stimulation with acoustic noise, SR would not be needed to optimize information transmission, and hence somatosensory noise would be tuned down, resulting in a transient vanishing of tinnitus, an effect referred to as residual inhibition.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Auditory phantom perception; Dorsal cochlear nucleus; Residual inhibition; Somatosensory projections; Speech perception; Stochastic resonance; Tinnitus; Zwicker tone

Tinnitus at the Junction of Traditional Medicine and Modern Technology - Mazurek, Birgit; Schulze, Holger; Schlee, Winfried; Dobel, Christian (Nutrients, 2023)
CRIS-Team Scopus Importer:2023-05-12

Tinnitus development is associated with synaptopathy of inner hair cells in Mongolian gerbils - Tziridis, Konstantin; Forster, Jan; Buchheidt-Dörfler, Isabelle; Krauß, Patrick; Schilling, Achim; Wendler, Olaf; Sterna, Elisabeth; Schulze, Holger (European Journal of Neuroscience, 2021)
Human hearing loss (HL) is often accompanied by comorbidities like tinnitus, which is affecting up to 15% of the adult population. Rodent animal studies could show that tinnitus may not only be a result of apparent HL due to cochlear hair cell damage but can also be a consequence of synaptopathy at the inner hair cells (IHCs) already induced by moderate sound traumata. Here, we investigate synaptopathy previously shown in mice in our animal model, the Mongolian gerbil, and relate it to behavioral signs of tinnitus. Tinnitus was induced by a mild monaural acoustic trauma leading to monaural noise induced HL in the animals, quantified by auditory brainstem response (ABR) audiometry. Behavioral signs of tinnitus percepts were detected by measurement of prepulse inhibition of the acoustic startle response in a gap-noise paradigm. Fourteen days after trauma, the cochleae of both ears were isolated, and IHC synapses were counted within several spectral regions of the cochlea. Behavioral signs of tinnitus were only found in animals with IHC synaptopathy, independent of type of HL. On the other hand, animals with apparent HL but without behavioral signs of tinnitus showed a reduction in amplitudes of ABR waves I&II but no significant changes in the number of synapses at the IHC. We conclude-in line with the literature-that HL is caused by damage to the IHC or by other reasons but that the development of tinnitus, at least in our animal model, is closely linked to synaptopathy at the IHC.
CRIS-Team WoS Importer:2021-07-09

Tinnitus is associated with increased extracellular matrix density in the auditory cortex of Mongolian gerbils - Tziridis, Konstantin; Maul, Antonia; Rasheed, Jwan; Krauß, Patrick; Schilling, Achim; Schulze, Holger (BMC Neuroscience, 2024)
Most scientists agree that subjective tinnitus is the pathological result of an interaction of damage to the peripheral auditory system and central neuroplastic adaptations. Here we investigate such tinnitus related adaptations in the primary auditory cortex (AC) 7 and 13 days after noise trauma induction of tinnitus by quantifying the density of the extracellular matrix (ECM) in the AC of Mongolian gerbils (Meriones unguiculatus). The ECM density has been shown to be relevant for neuroplastic processes and synaptic stability within the cortex. We utilized a mild monaural acoustic noise trauma in overall 22 gerbils to induce tinnitus and a sham exposure in 16 control (C) animals. Tinnitus was assessed by a behavioral response paradigm. Animals were separated for a presence (T) or absence (NT) of a tinnitus percept by a behavioral task. The ECM density 7 and 13 days after trauma was quantified using immunofluorescence luminance of Wisteria floribunda lectin-fluoresceine-5-isothiocyanate (WFA-FITC) on histological slices of the primary AC, relative to the non-auditory brainstem as a reference area. At both timepoints, we found that the WFA-FITC luminance of the AC of NT animals was not significantly different from that of C animals. However, we found a significant increase of luminance in T animals’ ACs compared to NT or C animals’ cortices. This effect was found exclusively on the AC side contralateral to the trauma ear. These results point to a hemisphere specific process of stabilization of synaptic connections in primary AC, which may be involved in the chronic manifestation of tinnitus.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Animal model; Auditory cortex; Extracellular matrix; Rodents; Tinnitus

Too Blind to See the Elephant? Why Neuroscientists Ought to Be Interested in Tinnitus - Knipper, Marlies; Mazurek, Birgit; Van Dijk, Pim; Schulze, Holger (Jaro-Journal of the Association For Research in Otolaryngology, 2021)
A curative therapy for tinnitus currently does not exist. One may actually exist but cannot currently be causally linked to tinnitus due to the lack of consistency of concepts about the neural correlate of tinnitus. Depending on predictions, these concepts would require either a suppression or enhancement of brain activity or an increase in inhibition or disinhibition. Although procedures with a potential to silence tinnitus may exist, the lack of rationale for their curative success hampers an optimization of therapeutic protocols. We discuss here six candidate contributors to tinnitus that have been suggested by a variety of scientific experts in the field and that were addressed in a virtual panel discussion at the ARO round table in February 2021. In this discussion, several potential tinnitus contributors were considered: (i) inhibitory circuits, (ii) attention, (iii) stress, (iv) unidentified sub-entities, (v) maladaptive information transmission, and (vi) minor cochlear deafferentation. Finally, (vii) some potential therapeutic approaches were discussed. The results of this discussion is reflected here in view of potential blind spots that may still remain and that have been ignored in most tinnitus literature. We strongly suggest to consider the high impact of connecting the controversial findings to unravel the whole complexity of the tinnitus phenomenon; an essential prerequisite for establishing suitable therapeutic approaches.
CRIS-Team Scopus Importer:2021-11-05
Keywords: attention; fast auditory processing; hyperacusis; parvalbumin positive interneuron; stress; tinnitus

Unilateral auditory cortex lesions impair or improve discrimination learning of amplitude modulated sounds, depending on lesion side - Schulze, Holger; Deutscher, Anke; Tziridis, Konstantin; Scheich, Henning (PLoS ONE, 2014)
A fundamental principle of brain organization is bilateral symmetry of structures and functions. For spatial sensory and motor information processing, this organization is generally plausible subserving orientation and coordination of a bilaterally symmetric body. However, breaking of the symmetry principle is often seen for functions that depend on convergent information processing and lateralized output control, e.g. left hemispheric dominance for the linguistic speech system. Conversely, a subtle splitting of functions into hemispheres may occur if peripheral information from symmetric sense organs is partly redundant, e.g. auditory pattern recognition, and therefore allows central conceptualizations of complex stimuli from different feature viewpoints, as demonstrated e.g. for hemispheric analysis of frequency modulations in auditory cortex (AC) of mammals including humans. Here we demonstrate that discrimination learning of rapidly but not of slowly amplitude modulated tones is non-uniformly distributed across both hemispheres: While unilateral ablation of left AC in gerbils leads to impairment of normal discrimination learning of rapid amplitude modulations, right side ablations lead to improvement over normal learning. These results point to a rivalry interaction between both ACs in the intact brain where the right side competes with and weakens learning capability maximally attainable by the dominant left side alone.
EVALuna2:19914

Weight statistics controls dynamics in recurrent neural networks - Krauß, Patrick; Schuster, Marc; Dietrich, Verena; Schilling, Achim; Schulze, Holger; Metzner, Claus (PLoS ONE, 2019)
Recurrent neural networks are complex non-linear systems, capable of ongoing activity in the absence of driving inputs. The dynamical properties of these systems, in particular their long-time attractor states, are determined on the microscopic level by the connection strengths w(ij) between the individual neurons. However, little is known to which extent network dynamics is tunable on a more coarse-grained level by the statistical features of the weight matrix. In this work, we investigate the dynamics of recurrent networks of Boltzmann neurons. In particular we study the impact of three statistical parameters: density (the fraction of non-zero connections), balance (the ratio of excitatory to inhibitory connections), and symmetry (the fraction of neuron pairs with w(ij)= w(ij)). By computing a 'phase diagram' of network dynamics, we find that balance is the essential control parameter: Its gradual increase from negative to positive values drives the system from oscillatory behavior into a chaotic regime, and eventually into stationary fixed points. Only directly at the border of the chaotic regime do the neural networks display rich but regular dynamics, thus enabling actual information processing. These results suggest that the brain, too, is fine-tuned to the 'edge of chaos' by assuring a proper balance between excitatory and inhibitory neural connections.
CRIS-Team WoS Importer:2019-04-23

β-Secretase BACE1 Is Required for Normal Cochlear Function - Dierich, Marlen; Hartmann, Stephanie; Dietrich, Nadine; Möser, Philip; Brede, Franziska; Johnson Chacko, Lejo; Tziridis, Konstantin; Schilling, Achim; Krauß, Patrick; Heßler, Sabine; Karch, Sandra; Schrott-Fischer, Anneliese; et al. (The Journal of Neuroscience, 2019)
Cleavage of amyloid precursor protein (APP) by β-secretase BACE1 initiates the production and accumulation of neurotoxic amyloid-β peptides, which is widely considered an essential pathogenic mechanism in Alzheimer's disease (AD). Here, we report that BACE1 is essential for normal auditory function. Compared with wild-type littermates, BACE1-/- mice of either sex exhibit significant hearing deficits, as indicated by increased thresholds and reduced amplitudes in auditory brainstem responses (ABRs) and decreased distortion product otoacoustic emissions (DPOAEs). Immunohistochemistry revealed aberrant synaptic organization in the cochlea and hypomyelination of auditory nerve fibers as predominant neuropathological substrates of hearing loss in BACE1-/- mice. In particular, we found that fibers of spiral ganglion neurons (SGN) close to the organ of Corti are disorganized and abnormally swollen. BACE1 deficiency also engenders organization defects in the postsynaptic compartment of SGN fibers with ectopic overexpression of PSD95 far outside the synaptic region. During postnatal development, auditory fiber myelination in BACE1-/- mice lags behind dramatically and remains incomplete into adulthood. We relate the marked hypomyelination to the impaired processing of Neuregulin-1 when BACE1 is absent. To determine whether the cochlea of adult wild-type mice is susceptible to AD treatment-like suppression of BACE1, we administered the established BACE1 inhibitor NB-360 for 6 weeks. The drug suppressed BACE1 activity in the brain, but did not impair hearing performance and, upon neuropathological examination, did not produce the characteristic cochlear abnormalities of BACE1-/- mice. Together, these data strongly suggest that the hearing loss of BACE1 knock-out mice represents a developmental phenotype.SIGNIFICANCE STATEMENT Given its crucial role in the pathogenesis of Alzheimer's disease (AD), BACE1 is a prime pharmacological target for AD prevention and therapy. However, the safe and long-term administration of BACE1-inhibitors as envisioned in AD requires a comprehensive understanding of the various physiological functions of BACE1. Here, we report that BACE1 is essential for the processing of auditory signals in the inner ear, as BACE1-deficient mice exhibit significant hearing loss. We relate this deficit to impaired myelination and aberrant synapse formation in the cochlea, which manifest during postnatal development. By contrast, prolonged pharmacological suppression of BACE1 activity in adult wild-type mice did not reproduce the hearing deficit or the cochlear abnormalities of BACE1 null mice.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Alzheimer's disease; auditory function; BACE1; BACE1 inhibitor NB-360; BACE1 knock-out mice; Neuregulin-1